Associations Between Rejection Sensitivity, Aggression, and Victimization: A Meta-Analytic Review. (January 2021) - Gao, Shuling; Assink, Mark; Liu, Tinting; Chan, Ko Ling; Ip, Patrick
Background: Rejection sensitivity (RS) is a personality disposition characterized by oversensitivity to social rejection; individuals who are sensitive to social rejection tend to anxiously or angrily expect, readily perceive, and overreact to it. The associations between (a) RS and aggression and (b) RS and victimization have been studied in recent years. However, the strength of these associations varied considerably between studies. This review aimed to synthesize the primary literature to improve our insight into these associations. Method: A comprehensive literature search yielded 52 studies (with a total of 66, 405 participants and producing 203 effect sizes) on the RS-aggression and RS-victimization associations. Three-level meta-analytic models were used to synthesize effect sizes and to examine potential moderators of the RS-aggression association and the RS-victimization association, respectively. Results: There was a small but significant association between RS and aggression (pooled r = .183; p < .001) and a slightly below moderate and significant association between RS and victimization (pooled r = .298; p < .001). The RS-aggression association was stronger for angry RS than for anxious RS and stronger for reactive aggression than for proactive aggression. Similar results were obtained in analyzing the longitudinal associations only. Conclusions: RS is significantly associated with aggression and victimization. The implications of the results for clinical practice as well as directions for future research are discussed.